Firefighting robot based on IoT and ban levels technique - Abdul Rahman, Ahmad Aizat; Janin, Zuriati; Sam, Rosidah; Masrie, Marianah; Gunawan, Teddy Surya; Abdul Rahman, Farah Diyana (IEEE, 2022)
Internet of Things (IoT) technology is known as a system where various sensors are connected to the Internet for various real-world applications. This paper presents a prototype fire fighting robot system. The system is designed and developed by implementing IoT and ban-level techniques for monitoring and control. The robot aims to eliminate human involvement and deliver an effective firefighting system. Arduino UNO V3 is used as a microcontroller, connected to a wireless mobile application, enabling the implementation of remote control. The robot is designed in such a way that inputs taken from the infrared flame sensor, water level sensor, and smoke level detector are used to determine the movement of the water spray nozzle so that it will be directed to the fire source precisely. A prototype was successfully designed and the functionality of the system was tested. The results show that the IoT infrastructure can successfully track and control the movement of the robot and the spray direction of the nozzle.